A Comparative Study About Physical Properties of Copper Oxide and Zinc Oxide Nanoparticles on Fagus orientalis L. as Bioindicator - Isinkaralar, Kaan; Isinkaralar, Oznur; Özel, Halil Barış; Şevik, Hakan (Springer Science and Business Media LLC, 2024)
Nanoparticles (NPs) have recently begun to be used extensively in many areas of our lives. It is stated that the resulting NPs pollution will affect even the most remote ecosystems on the Earth. Therefore, determining the effects of NPs on diverse ecosystems is a research topic of interest. From this perspective, current researches on NPs affecting forest ecosystems and forest trees are very scarce. The aim of this investigation was to reveal the inhibitory and toxic properties of CuO and ZnO-NPs on oriental beech seed germination parameters and identify the toxic threshold values of CuO and ZnO-NPs. Therefore, the oriental beech (Fagus orientalis L.) seeds obtained from ten populations (P1 to P10) were treated with CuO and ZnO-NPs as single compounds at concentrations of 200, 400, 600, 800 and 1000 mg/L and germination rate (GR), germination percentage (GP), root collar diameter (RCD), plumula length (PL), radicle thickness (RT) and radicle diameter (RD) were determined for 35 days. The water containing CuO-ZnO NPs as a single compound at 1000 mg/L negatively affected all growth in general. The significant decrease in our study occurred at P9. The CuO-ZnO NPs were reduced in GP, RCD, PL, RT, and RD as 3.5-4.2%; 11.2-0.1%; 9.1-36.4%; 23.07-38.46%; and 39.29-17.86%, while GR enhanced as 21.46-20.09%. It was found that water with a low concentration of NP (200 mg/L) is suitable for irrigation of seeds grown in soil media and does not have a significant toxic effect on the growth and uptake of metal ions. The findings and limitations of the present research allow us to assess the feasibility of reusing NP-contaminated water in agriculture. Nevertheless, further research is needed to understand the toxic effects of NP mixtures on growth and absorption mechanisms.
Keywords: Seeds Grown; Nanoparticle Pollution; Irrigation; Wastewater Use; Germination Parameters